2014
DOI: 10.1371/journal.pone.0111796
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Quality of Guidelines for Myasthenia Gravis with the AGREE II Instrument

Abstract: BackgroundClinical practice guidelines (CPGs) are systematically developed statements to assist practitioners in making decisions about appropriate healthcare in specific clinical circumstances. The methodological quality of CPGs for myasthenia gravis (MG) are unclear.ObjectiveTo critically evaluate the methodological quality of CPGs for MG using AGREE II instrument.MethodA systematical search strategy on PubMed, EMBASE, DynaMed, the National Guideline Clearinghouse (NGC) and the Chinese Biomedical Literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
(29 reference statements)
2
18
0
2
Order By: Relevance
“…Armstrong et al reported similar results (45%) after conducting an evaluation of osteoporosis guidelines focusing on physical activity and safe movement [18]. This domain scored low in several other studies [19, 20, 22, 23], with few exceptions [21]. According to AGREE II, the evaluation of “editorial independence” considers two aspects related to funding bodies or potential authors’ competing interests that may influence the guideline content.…”
Section: Discussionmentioning
confidence: 95%
“…Armstrong et al reported similar results (45%) after conducting an evaluation of osteoporosis guidelines focusing on physical activity and safe movement [18]. This domain scored low in several other studies [19, 20, 22, 23], with few exceptions [21]. According to AGREE II, the evaluation of “editorial independence” considers two aspects related to funding bodies or potential authors’ competing interests that may influence the guideline content.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, the Appraisal of Guidelines Research and Evaluation instrument [21] version II (AGREE II), published in 2009, has been extensively used, validated in several languages, and covers essential information for comprehensive CPG evaluation [19,20]. Several studies worldwide have been conducted for assessing CPG quality using the AGREE II [911,1618,2225]; however, very little is known regarding CPG quality among low income countries [10]. To date, only one study has evaluated CPG quality in Brazil [18], and none have critically assessed CPGs for NCD treatment quality within a Brazilian sample.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only the author performed the quality assessments, implying a risk of bias. However, the AGREE II instrument has been shown to have adequate levels of validity and reliability , and previous studies indicate high interrater reliability when multiple assessors are used . This, combined with the fact that two separate instruments were used to assess methodological quality, strengthens the findings concerning poor quality.…”
Section: Discussionmentioning
confidence: 92%